ARTISTICITY IN THE STORY GENRE - Sevara Abdumalikovna Suleymanova (Web of Journals Publishing, 2024)
If we take into account that there are always psychological problems in the short story genre, the essence of the problem becomes clear. It is clear that only one-sided study of the problem does not fit the dimensions of our research.
Keywords: Short story. genre, spirituality, theory, prose, literary studies, poetics.